CANVA COMO HERRAMIENTA DIDACTICA EN EL APRENDIZAJE DE LOS ESTUDIANTES DE LA CARRERA DE EDUCACIÓN BÁSICA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERIODO OCTUBRE 2023- MARZO 2024 - GUZMAN CASPI MAYCOL ESTIVEN (2024)
The purpose of this study is based on the influence of canva as a didactic tool for the learning of students of the basic education career of the Technical University of Babahoyo, the study focuses on knowing how this platform, known for its ease of use and Versatility in the creation of visual resources can improve students' understanding and retention of content, thus promoting creativity and their active participation in the classroom. The estimated population for this research was 694, taking a sample of 120 students belonging to the basic education major. The type of research was descriptive with a mixed approach, for this project the survey technique was used in which a questionnaire of 10 closed questions and observation were carried out to provide us with concrete and real data on the behavior of the study phenomenon to reach a deeper and more objective understanding. It is concluded that the use of canva intervenes positively in active participation, the ease of use it offers motivates students to interact with the elements that make up this platform, given that the interactivity and creativity offered by this tool helps to stimulate commitment in students